AN ANALYSIS OF MORAL VALUES IN THE MALEFICENT : “MISTRESS OF EVIL” MOVIE - Sinaga, Juwita Boneka (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2023)
Abstract The objective of this research is to find out the kinds of moral values in Maleficent: "Mistress of Evil" movie. The researcher uses Hartmann's theory to analyze the kinds of moral values in the movie. The research design used in this research is descriptive qualitative research, the data sources are from the utterances and the scene of Maleficent: "Mistress of Evil" Movie and theory from books, e- books, journals. Data collection procedure uses document methods and data analysis procedure uses data reduction, data display and conclusion drawing. The results showed that the movie Maleficent: "Mistress of Evil", based on Hartmann theory found 9 kinds of moral values consisting of Justice, Courage, Self-Control, Brotherly Love, Truthfulness, Trustworthiness, Fidelity, Personality and Personal Love. and there are 21 data found in the movie regarding Kinds of moral values. And based on the data, can be determined that the most dominant moral value in the movie are Brotherly love and Fidelity.